Performances comparison of 12S-14P field excitation flux switching motor with overlap and non-overlap windings for hybrid electric vehicles - Husin, Zhafir Aizat (2014)
Hybrid electric vehicles (HEVs), using combination of an internal combustion engine (ICE) and one or more electric motors, are widely considered as the most promising clean vehicles. The only machine that already installed for HEVs is interior permanent magnet synchronous machine (IPMSM) where it has developed to enhance power density of the machine. Despite of fine operated and superior performances, this machine do not miss approached by deficiency for instance IPMSM now have complex form and configuration that give difficulty to undertake the process of optimization. Moreover, the use of PM will result in a constant state of flux and cannot be controlled as well a burden because of expensive rare earth magnet prices. Therefore, a new candidate of field excitation flux switching machine (FEFSM), in which the uses of PM are totally excluded with rugged rotor structure suitable for high-speed operation and the ability to keep high torque and power density is proposed and examined in this paper. Under some design specifications, design principles and performances of 12S-14P FEFSMs with overlap and non-overlap FEC and armature coil windings are presented. The profile of flux linkage, induced voltage, cogging torque, torque and power characteristics are observed based on 2D finite element analysis (FEA).